BitTorrent dengan Reactive Routing pada Software-Defined Network - Landika Hari Suganda; Widhi Yahya; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
BitTorrent is a file sharing application that uses a peer-to-peer mechanism to distribute pieces of files (chunk). The process of determining the seeder is still done randomly, so to get the optimal seeder needs to be optimistic unchoking. In this study BitTorrent is implemented with software a defined-network concept that separates the control plane and data plane to facilitate application development. The reactive routing controller creates a flow table that use to connect between the peers and determines the peer list as the nearest seeder based on the number of hop using the Dijkstra algorithm. The simulation results show that the system can select some of the nearest seeders by reactive routing based on the number of hops traversed. we use BitTornado for application BitTorrent client and use Pybtracker for application of tracker. Here we observe download rate and throughput generated on BitTorrent application with random seeder and BitTorrent application that has been modified with controller. The test results obtained an average value of download rate 4785.3 Kbps with 25 seconds distribution time on 3 random seeders, 6378.3 Kbps with a distribution time of 17 seconds on 5 random seeders, 6721.9 Kbps with 18 seconds distribution time on 7 random seeders and 5990.8 Kbps with time distribution of 18 seconds on 3 seeders, 6732.1 Kbps with 15 seconds distribution time on 5 seeders, 7656.53 Kbps with 15 seconds distribution time on 7 seeders.